DATA CENTERS, ENERGY AND REGULATION: LEGAL AND ECONOMIC CHALLENGES FOR DIGITAL INFRASTRUCTURE IN BRAZIL - Ferraz, Daniel Amin; Viegas, Paulo Roberto Alonso (Seven Editora, 2026)
This article analyzes the legal and economic challenges related to the installation and operation of data centers in Brazil, considering their nature as critical infrastructure and their growing importance in the digital economy. It examines energy demand, technological alternatives for continuous electricity supply, as well as environmental and regulatory impacts. Legislative initiatives in progress and public policy proposals aimed at consolidating a specific regulatory framework are evaluated. The thesis defended is that Brazil’s competitiveness in the data economy depends on the creation of a stable regulatory environment, integrated with energy and environmental policies, capable of guaranteeing legal certainty and attracting long-term investments. DOI: https://doi.org/10.56238/sevened2026.008-005